Bilateral V-Y medial fasciocutaneous thigh flap in perineal reconstruction for hidradenitis suppurativa: Case report - Alexander Fabricio Vicente-Rivas; Vitor Penteado Figueiredo Pagotto; Sabrina Buscariol; Marilia Ito; Rolf Gemperli (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: Hidradenitis suppurativa (HS) is a chronic inflammatory disease that preferentially affects the intertriginous skin and is associated with numerous systemic comorbidities. The perineal area is the second most commonly affected area after the armpit. Wide excision is the treatment most likely to achieve better results with a lower risk of recurrence. With extensive surgical excision, flap closure offers a greater likelihood of definitive treatment. Some flaps have been described to reconstruct defects in the perineal region after cancer, but few have been studied in treating HS. Case Report: A 43-year-old woman with perineal HS underwent resection of the lesions and reconstruction with a bilateral V-Y medial thigh fasciocutaneous flap to treat the disease. The flap allowed complete closure of the total perineum without serious complications. Conclusion: This case shows that it is useful and practical to use the V-Y medial thigh fasciocutaneous flap for perineal reconstruction after wide resections of skin, apocrine glands, and hair follicles in the treatment of HS, offering good skin coverage and subcutaneous cellular tissue with supply reliable vascular flap, which avoids sequelae associated with muscle sacrifice and reaches larger dimensions than other flaps, and can be considered in selected cases as an alternative in the surgical treatment of perineal HS.